Pemberdayaan dan Pendampingan Anak Terlantar di Panji Berbakat Anak di Kelurahan Baru Ulu Balikpapan - Budha Maryanti; A. Asni B (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2019)
In some corners of the city, it is often found abandoned children who roam around school hours and engage in less productive activities that disturb the peace of the community. which makes them fall into drugs. This should be a concern of the community starting from the household to the city government. In Balikpapan, specifically the